PENGGUNAAN METODE CERTAINTY FACTOR PARALEL UNTUK MENDETEKSI HAMA DAN PENYAKIT PADA TANAMAN KAKAO - fitria kenali (Jurnal Informatika, 2011)
Expert system is a system that attempted to adopt human knowledge to computer, so that computers can solve problems like the experts . A good expert system designed to solve a particular problem by mimicking the work of the experts/specialists. Kokoa is a plant that is relatively easy way of planting and does not require land that is so extensive that these plants tend to be planted in demand both in plantations and the environment around the house. Indonesia has a tropical climate which is very supportive of this plant to grow and flourish. Parallel Certainty Factor method is one method of expert system to determine the value of confidence based on the value of the elements of conviction entered by an expert and a user. The values ​​entered are calculated based on predefined rules and concluded the final value of the percentage of belief in diseases of the kokoa plant. Key words: Certainty Factor Parallel, System, Kokoa